The younger generation's magazines in the eyes of the communist ideologues - Gabrič, Aleš (Array, 2019)
The contribution analyses the increasing criticism, voiced by the younger generation of Slovenian intellectuals from the first post-war years until the end of the 1950s. The critical attitude towards the pressing social issues started developing in the beginning of the 1950s, as Mladinska revija – the first post-war literary magazine, published between 1946 and 1951 – was still subject to thorough scrutiny by the authorities. In the period of its successor – the Beseda magazine between 1951 and 1957 – certain more radical debates or critiques of the existing situation were already published. This publication stopped coming out in 1957. However, contrary to what the authorities had expected, a similar circle of the associates of this magazine's successor, the Revija 57 magazine (published in 1957 and 1958), was even more critical of the situation in the state. This contribution thus follows two parallel processes: on the one hand the increasingly critical attitude of the younger-generation intellectuals towards the authorities; and on the other hand the mounting pressure that the authorities exerted against magazines that published critical texts. At first the publications were merely the focus of political disapproval, followed by the abolishment of subsidies and thus consequently the cancellation of the magazines; while towards the end of the 1950s we can already come across a judicial process against an author of socially-critical articles. The leading politicians at the end of the period under consideration already saw the younger generation of intellectuals as the (cultural) opposition.